Penanaman Karakter Positif Siswa Melalui Pembiasaan: Studi Kasus di SMP Negeri 40 Kota Bandung - Eman Puroman; Feri Indra; Dul Wahid Toha (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to Describe the implementation of habituation activities carried out at SMP Negeri 40 Bandung in order to instill positive character in students. Identify positive character values developed through habituation activities in the school environment. This study uses a qualitative approach with a case study method. Case study is a research approach used to generate in-depth and multi-faceted understanding of complex problems in real-life contexts. In other words, case study is a research design that is widely used in various disciplines, especially in the social sciences, which has the main principle of exploring an event or phenomenon in depth in a natural context. The results of the study indicate that the instillation of positive character through habituation at SMP Negeri 40 Bandung can be done through various activities, which are repeated with the term habituation including routine, programmed, and incidental activities. It is hoped that these activities will be able to form character values in children, such as honesty, discipline, responsibility, and hard work. The success of implementing character education through habituation in schools requires support from various parties, from teachers and principals to parents.